Simple D [X, Y; σ, а]-modules - Bavula , V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The article classifies simple modules over a generalized Weyl algebra of degree 1 with basis ring D that is a commutative domain with limited minimality condition.